Concurrent validity of a rugby-specific Yo-Yo intermittent recovery test (level 1) for assessing match-related running performance - Dobbin, N.; Highton, J.; Moss, S. L.; Hunwicks, R.; Twist, C. (The Journal of Strength and Conditioning Research, 2021)
This study investigated the concurrent validity of a rugby-specific high-intensity intermittent running test against the internal, external, and perceptual responses to simulated match play. Thirty-six rugby league players (age 18.5 ± 1.8 years; stature 181.4 ± 7.6 cm; body mass 83.5 ± 9.8 kg) completed the prone Yo-Yo Intermittent Recovery Test (Yo-Yo IR1), of which 16 also completed the Yo-Yo IR1, and 2 × ~20 minute bouts of a simulated match play (rugby league match simulation protocol for interchange players [RLMSP-i]). Most likely reductions in relative total, low-speed and high-speed distance, mean speed, and time above 20 W/kg (high metabolic power [HMP]) were observed between bouts of the RLMSP-i. Likewise, rating of perceived exertion (RPE) and percentage of peak heart rate (%HRpeak) were very likely and likely higher during the second bout. Pearson's correlations revealed a large relationship for the change in relative distance (r = 0.57-0.61) between bouts with both Yo-Yo IR1 tests. The prone Yo-Yo IR1 was more strongly related to the RLMSP-i for change in repeated sprint speed (r = 0.78 cf. 0.56), mean speed (r = 0.64 cf. 0.36), HMP (r = 0.48 cf. 0.25), fatigue index (r = 0.71 cf. 0.63), %HRpeak (r = -0.56 cf. -0.35), RPEbout1 (r = -0.44 cf. -0.14), and RPEbout2 (r = -0.68 cf. -0.41) than the Yo-Yo IR1, but not for blood lactate concentration (r = -0.20 to -0.28 cf. -0.35 to -0.49). The relationships between prone Yo-Yo IR1 distance and measures of load during the RLMSP-i suggest that it possesses concurrent validity and is more strongly associated with measures of training or match load than the Yo-Yo IR1 using rugby league players.